Distribution and congener profiles of short-chain chlorinated paraffins in indoor/outdoor glass window surface films and their film-air partitioning in Beijing, China. (February 2016) - Gao, Wei; Wu, Jing; Wang, Yawei; Jiang, Guibin
Abstract: Short-chain chlorinated paraffins (SCCPs) are a group of n-alkanes with carbon chain length of 10–13. In this work, paired indoor/outdoor samples of organic films on window glass surfaces from urban buildings in Beijing, China, were collected to measure the concentrations and congener distributions of SCCPs. The total SCCP levels ranged from 337 ng/m 2 to 114 μg/m 2, with total organic carbon (TOC) normalized concentrations of 365 μg/m 2 –365 mg/m 2 . Overall, the concentrations of SCCPs on the interior films were higher than the concentrations on the exterior films, suggesting an important indoor environmental exposure of SCCPs to the general public. A significant linear relationship was found between the SCCP concentrations and TOC, with a correlation coefficient of R = 0.34 ( p  < 0.01). A film-air partitioning model suggests that the indoor gas-phase SCCPs are related to their corresponding window film levels. Highlights: High levels of SCCPs were found both in the window surface films and in indoor air. Congener group abundance profiles varied between indoor and outdoor films. The relationship of different building characteristics and SCCPs distributions were studied. Film-air partitioning study of SCCPs suggested that indoor gas-phase SCCPs are related to their corresponding film levels. Abstract : High concentrations of short chain chlorinated paraffins (SCCPs) were found in window film and in indoor air, indicating the relative high exposure levels of short chain chlorinated paraffins (SCCPs) for the general populations in indoor environment in Beijing China.